Talk to Me! Real-Time Audio-Conferencing and the Changing Roles of the Teacher and the Learner in a 24/7 Environment - Kötter, Markus; Shield, Lesley (Proceedings of the International Conference on Networked Learning, 2000)
The model of distance learning in which Open University [OU] language learners take part is the ' traditional' one for the OU - print, video, audio and face-to-face tutorials. However, since the presentation of its first language course in 1995, the Centre for Modern Languages [CML] has actively investigated alternative means for the provision of language teaching and learning. This paper describes the projects undertaken over the past five years with a particular focus on the most recent studies, the Fluent Project [The establishment of a Framework for Language Use in Environments embedded in New Technologies] which used synchronous voice-over-Internet conferencing with learners of French and German and recent trials with Lyceum, an integrated audiographics package. We briefly discuss the role of the tutor in such virtual learning environments [VLEs] and we summarise learner responses and learning outcomes. Data collected include copies of student e-mail, audio recordings of the individual scheduled sessions, tutor observations and learner feedback obtained through a series of questionnaires.